USP35 promotes hepatocellular carcinoma proliferation through GASC1-mediated ROCK2 upregulation - Gen Chen; Yong Shi; Shuaimin Zhang; Xiaofang Zhang; Guohui Li; Chenghang Jiang (Translational Oncology)
Ubiquitin-specific protease 35 (USP35) regulates the oncogenic process of various cancers by stabilizing target proteins through deubiquitination. However, the function of USP35 in hepatocellular carcinoma (HCC) remains unclear. Our results demonstrated that USP35 was significantly over-expressed in HCC. The upregulation of USP35 was connected with a larger tumor size and weight. Additionally, the function of USP35 in promoting HCC proliferation was demonstrated by multiple gain/loss functional assays. Moreover, we found a positive correlation between USP35 and rho-associated coiled-coil-containing protein kinase-2 (ROCK2) expression levels, and USP35 promotes proliferation of HCC cells through ROCK2. We also identified the underlying mechanism by which USP35 promotes ROCK2 expression through binding to gene amplified in squamous cell carcinoma 1 (GASC1) and diminishing GASC1 ubiquitination and degradation. Overall, our findings identified a critical function of USP35 in HCC proliferation, suggesting USP35 may be a potential therapeutic target for HCC oncogenicity.